2020
DOI: 10.3390/app11010001
|View full text |Cite
|
Sign up to set email alerts
|

Blockchain-Based Multimedia Content Protection: Review and Open Challenges

Abstract: In this paper, we provide a holistic survey of multimedia content protection applications in which blockchain technology is being used. A taxonomy is developed to classify these applications with reference to the technical aspects of blockchain technology, content protection techniques, namely, encryption, digital rights management, digital watermarking and fingerprinting (or transaction tracking), and performance criteria. The study of the literature reveals that there is currently no complete and systematic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(23 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…− Reconstruct the extracted watermark (W") by using inverse SVD the orthogonal matrices of original image (UW and VhW) with the extracted singular vector (SW') (13).…”
Section: Watermark Validationmentioning
confidence: 99%
“…− Reconstruct the extracted watermark (W") by using inverse SVD the orthogonal matrices of original image (UW and VhW) with the extracted singular vector (SW') (13).…”
Section: Watermark Validationmentioning
confidence: 99%
“…The authors of [ 41 ] proposed a taxonomy that incorporates both technical and application information and could help academics construct blockchain-based multimedia copyright protection systems. The study also explored several technical issues and suggested future research directions.…”
Section: Related Surveysmentioning
confidence: 99%
“…Omar S. Saleh, et.al (12) , proposed a blockchain technology that enhanced certificate verification in the education domain. Amna Qureshi, et.al (13) , proposed, reviewed comments and open challenges of blockchain-based multimedia content protection applications. Robert Alexandru Dobre, et.al (14) , proposed, blockchain-enabled Image copyright protection using JPEG resistant digital signature.…”
Section: Related Workmentioning
confidence: 99%